2003
DOI: 10.1530/eje.0.1490421
|View full text |Cite
|
Sign up to set email alerts
|

Absence of exercise-induced variations in adiponectin levels despite decreased abdominal adiposity and improved insulin sensitivity in type 2 diabetic men

Abstract: Objective: We investigated the effect of an intensive training program on fasting leptin and adiponectin levels. Methods: Sixteen middle-aged men with type 2 diabetes were randomly assigned to either a training or control group. The training program consisted of 8 weeks of supervised endurance exercise (75% VO 2peak , 45 min) twice a week, with intermittent exercise (five 2 min exercises at 85% VO 2peak separated by 3 min exercises at 50% VO 2peak ) once a week, on an ergocycle. Results: Training decreased abd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
146
1
7

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(168 citation statements)
references
References 20 publications
13
146
1
7
Order By: Relevance
“…Twelve weeks of endurance and circuit weight training did not change serum adiponectin concentrations, in accordance with the general consensus (3,(8)(9)(10)(11). There are only few endurance-training studies that have reported different findings (12-15).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Twelve weeks of endurance and circuit weight training did not change serum adiponectin concentrations, in accordance with the general consensus (3,(8)(9)(10)(11). There are only few endurance-training studies that have reported different findings (12-15).…”
Section: Discussionsupporting
confidence: 85%
“…However, there is still controversy with regard to the effects of endurance training on adiponectin. For example, different authors have demonstrated no change (3,(8)(9)(10)(11), an increase (12)(13)(14) or a decrease (15) in adiponectin following different training protocols.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 In these studies, the training period of 8 weeks was 33% shorter, but the relative exercise intensity and mode of exercise training (i.e., cycle ergometer) were relatively has not been well tested, and future studies are needed to identify potential changes in the expression of proinfl ammatory cytokines in abdominal adipose tissue and their relationship to changes in hepatic and peripheral insulin sensitivity.…”
Section: Peak Oxygen Consumption and Maximum Work Outputmentioning
confidence: 99%
“…Kraemer et al (15) investigated the acute effects of short-term, running exercise on plasma adiponectin secretion in healthy subjects but observed no changes. Other studies, exploring the more long-term benefits of exercise training, also reported no changes in basal plasma adiponectin concentration (16)(17)(18)22). In contrast, Kriketos et al (19) recently reported substantially elevated fasting plasma adiponectin levels (260% above baseline values) after 2-3 bouts of low to moderate intensity exercise.…”
Section: Introductionmentioning
confidence: 99%